A proposed summer seminar-workshop for intermediate science teachers in the utilization of local materials for the production of science equipment - Domingo, Leo Ver 1943- (s.n.], 1973)
This paper attempts to help teachers device some science equipments out of local materials. These equipments are necessary in carrying out successfully the activities suggested by the Bureau of Public Schools intermediate science curriculum guides.